L’art comme forme symbolique - Audrey Rieber (Appareil)
Cassirer thinks of the musical art as a symbolic form. That allows him to put the emphasis both on the composer’s activity and on the audience’s, that is to say to reject the theory of inspiration and to bring up the idea of configuration. What is specific to music is that it can discover pure forms of the mind. The theory of imitation (and one of its variants: the theory of expression) and the moralizing conception of art are therefore irrelevant. Finally, the culture philosopher’s reflexion on music must be related to the philosophy of mind. Music becomes a path to freedom when, and only when, it reaches the stage of pure symbolic.